Internalization of Character Education Based on National Hero Example in Developing Nationalism - Adnyani, Ni Ketut Sari; Budiarta, I Wayan (Center of Language and Cultural Studies, 2021)
The purpose of this study was to analyze the internalization of character education based on exemplary national heroes in learning citizenship education in elementary schools in Karangasem Regency, Bali.